Cost-effectiveness of polatuzumab vedotin in relapsed or refractory diffuse large B-cell lymphoma. Issue 14 (5th December 2020) - Patel, Kishan K.; Isufi, Iris; Kothari, Shalin; Foss, Francine; Huntington, Scott
Abstract: A recent phase II trial showed that use of polatuzumab vedotin in combination with bendamustine plus rituximab (Pola-BR) in transplant-ineligible patients with relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL) resulted in longer progression-free survival and overall survival compared to bendamustine plus rituximab (BR) alone. In this study, we constructed a Markov model to assess the cost-effectiveness of Pola-BR versus BR in transplant-ineligible R/R DLBCL. We calculated the incremental cost-effectiveness ratio (ICER) of each treatment strategy from a US payer perspective, using a lifetime horizon and a willingness-to-pay threshold of 100, 000 per quality-adjusted life-year (QALY). Use of Pola-BR was associated with an incremental cost of 92, 641 compared to BR alone (200, 905 vs 108, 265, respectively), an incremental effectiveness of 1.76 QALYs (2.35 vs 0.59 QALYs, respectively), and an ICER of 52, 519/QALY. These data suggest that use of Pola-BR for R/R DLBCL is likely to be cost-effective compared to BR alone.